Contribuição ao gerenciamento de recursos hídricos do Rio Piracicaba - BARP, Ana Rosa Baganha (Universidade Estadual de Campinas, 2018)
This work deals with a network flow optimization problem applied to the Piracicaba river system. A mathematical optimization method which gives great computational efficiency was selected. The aim is to help the management and operation of hydrografic basins geared to the control of the quality and quantity of the water. Computational mathematical models were chosen due to their speedy and efficient aid to decision making. The problem was handled by adopting the multiobjective formulation of the Weight Method and a networks flow optimization algorithm coupled with a piece-wise linear objective function. At was verified that the river system responds satisfactorily as long as the flow of a twenty-four month's period is known in advance (deterministc flows) and with due manipulation of the storages and differentiation of the storages with time. The systemic vision the models provides is an alternative approach to the traditional studies that evaluate the benefits the hydraulic structures in the punctual form